Exposure pathways (diet, dissolved or particulate substrate) of rare earth elements to aquatic organisms - Ashlyn Kernaghan; Duc Huy Dang (Ecotoxicology and Environmental Safety)
The global extraction and use of rare earth elements (REEs) continue to rise as they are implemented in technologies that improve human and environmental livelihoods. However, the general understanding of transfer processes and fates of REEs in aquatic systems remains limited. Here, we aim to determine the REEs' main exposure pathways, e.g., particulate fraction, diet, or dissolved (ionic) fractions, to three benthic and three pelagic organisms. They were maintained under laboratory conditions and exposed to natural river water, with or without a sand substrate and an adapted diet. The organisms include northern clearwater crayfish (Faxonius propinquus), chinese mystery snail (Cipangopaludina chinensis), black sandshell mussel (Ligumia recta), striped shiner minnows (Luxilus chrysocephalus), Daphnia magna, and Euglena gracilis. The combined results of REE concentrations, fractionations, and anomalies highlighted that pelagic organisms are characterized by heavy REEs enrichment indicating they mainly uptake REEs in the dissolved form with high bioaccumulation potential, i.e., bioconcentration (BCF) > 1 and diet accumulation factors (DAF) < 1. Pelagic organisms exhibited relatively low REE concentrations in their tissues ([La] ranging from 4.6 to 57.7 µg kg−1 in minnows, 18.4 µg kg−1 in whole body D. magna, and 32.2 µg kg−1 in E. gracilis). On the other hand, snails and mussels were enriched in light REEs showing they mainly uptake REEs through their respective diets and particulate sand substrate. Relative to pelagic organisms, mussels and snails have higher DAFs (161.2 and 18.6, respectively) and REE levels in their soft tissues ([La] of 5700 µg kg −1 and 650 µg kg −1, respectively), but DAF for crayfish remains < 1. In summary, under environmental-relevant conditions, the six aquatic organisms has the potential to accumulate REEs through various uptake pathways. Nevertheless, our results confirming preferential uptake pathways of the six organisms can help select appropriate species in future studies to monitor REE exposure from vaious fractions: dissolved, particulate forms or in the food webs (i.e., diet).